Empowering Pedagogical Competences of Islamic Education Department Students in an Inclusive Setting Learning - Sari, Ratna; Daneska, Elsa; Hartanti, Adinda (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2020)
This research explores the effectiveness of using the Workshop methodology in enhancing pedagogical competences of the Islamic Education Department (Pendidikan Agama Islam/ PAI) teacher candidates in organizing an inclusive setting learning. Pedagogical competence indicators in this study consist of five components; (1) Teacher’s understanding towards students, (2) Ability to design and organize learning, (3) Utilization of technology in learning activities, (4) Implementation of learning outcomes evaluation, (5) Development of student competencies. The workshop is one of the training methods that can be used to improve the pedagogical competence of PAI teacher candidates. This study utilizes a post-test only experiment method. The research subjects consist of the control and experimental class. The post-test was carried out in the control and experiment class, while data collected through a test, observation, and documentation. Furthermore, the data is analyzed by content analysis of the post-test and observation results of the workshop program implementation.